2021
DOI: 10.1002/pne2.12050
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perception, knowledge, and use of neonatal pain assessment

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…36 However, clinical training may also be important for nurses to increase the application of SOPs. 16,19,22,34 In general, we did not find any difference between the physicians' and the nurses' assessment regarding the application of SOPs for PM. In NICUs with written SOPs for PM, physicians and nurses reported equally that these SOPs were applied.…”
Section: Ta B L E 1 Participants' Characteristicsmentioning
confidence: 51%
See 4 more Smart Citations
“…36 However, clinical training may also be important for nurses to increase the application of SOPs. 16,19,22,34 In general, we did not find any difference between the physicians' and the nurses' assessment regarding the application of SOPs for PM. In NICUs with written SOPs for PM, physicians and nurses reported equally that these SOPs were applied.…”
Section: Ta B L E 1 Participants' Characteristicsmentioning
confidence: 51%
“…In previous research, nurses named insecurity and perceived insufficient knowledge as barriers to using pain scales and managing patient pain. 19,34 Our results showed that nurses with longer working experience applied SOPs for PM more often in their clinical practice than nurses with less working experience. This result is consistent with the findings of Rolfe et al 24 They showed that nurses used their own clinical experience beside national guidelines and local policies as an important influencing factor on their clinical practice.…”
Section: Ta B L E 1 Participants' Characteristicsmentioning
confidence: 70%
See 3 more Smart Citations